(1)H, (13)C and (15)N resonance assignments for the response regulator CheY3 from Rhodobacter sphaeroides. - Varela, L; Bell, C; Armitage, J; Redfield, C (Springer Verlag, 2016)
Rhodobacter sphaeroides has emerged as a model system for studies of the complex chemotaxis pathways that are a hallmark of many non-enteric bacteria. The genome of R. sphaeroides encodes two sets of flagellar genes, fla1 and fla2, that are controlled by three different operons. Each operon encodes homologues of most of the proteins required for the well-studied E. coli chemotaxis pathway. R. sphaeroides has six homologues of the response regulator CheY that are localized to and are regulated by different clusters of chemosensory proteins in the cell and have different effects on chemotaxis. CheY6 is the major CheY stopping the fla1 flagellar motor and associated with a cytoplasmically localised chemosensory pathway. CheY3 and CheY4 are associated with a membrane localised polar chemosensory cluster, and can bind to but not stop the motor. CheY6 and either CheY3 or CheY4 are required for chemotaxis. We are using NMR spectroscopy to characterise and compare the structure and dynamics of CheY3 and CheY6 in solution. We are interested in defining the conformational changes that occur upon activation of these two proteins and to identify differences in their properties that can explain the different functions they play in chemotaxis in R. sphaeroides. Here we present the (1)H, (13)C and (15)N assignments for CheY3 in its active, inactive and Mg(2+)-free apo form. These assignments provide the starting point for detailed investigations of the structure and function of CheY3.